Examining School Acceptance Processes for Children with Intellectual Disabilities in Indonesian Elementary Education - Yulfitri, Dewi; Purwanta, Edi (Journal of Innovation and Research in Primary Education, 2025)
Despite global commitments to inclusive education, children with intellectual disabilities continue to face significant barriers in accessing mainstream educational opportunities. Limited research has examined the specific processes and stakeholder attitudes that influence school acceptance decisions for these students, particularly in Indonesian elementary school contexts. This qualitative case study examined school acceptance processes for children with intellectual disabilities at SD Integral Hidayatullah Sangatta, Indonesia. Data collection involved in-depth interviews with six participants (principal, vice-principals, teacher, parent, and student), participant observation, and document analysis over three months. Data analysis followed the Miles and Huberman framework, employing multiple triangulation methods to ensure validity. The study revealed seven key findings: absence of specialized admission procedures, reactive identification processes occurring only after enrollment, limited professional support systems, minimal systematic curriculum adaptations, positive stakeholder attitudes despite structural challenges, informal parent-school communication patterns, and lack of collaboration with external professionals. While teachers and peers demonstrated accepting attitudes toward students with intellectual disabilities, institutional support systems remained inadequate. Identification of special needs occurred reactively after classroom difficulties emerged, rather than through proactive screening procedures. Findings demonstrate significant gaps between inclusive education ideals and practical implementation. The study contributes theoretical understanding by illustrating how teacher agency theory, the Family Stress Model, and multicultural education frameworks intersect to explain implementation complexity. Results suggest that positive attitudes, while necessary, are insufficient without corresponding institutional support systems, systematic professional development, and structured collaboration frameworks. Effective inclusive education requires comprehensive systemic changes addressing institutional policies, professional development, resource allocation, and family support systems. Future research should examine comparative cases across diverse contexts and investigate longitudinal outcomes of different inclusion approaches.